2005
DOI: 10.1063/1.1906329
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature quantum effect in silicon nanoparticles obtained by low-energy ion implantation and embedded in a nanometer scale capacitor

Abstract: In this article, we present the room-temperature current-voltage characteristics of a nanometer scale (100×100nm2) metal-oxide-semiconductor capacitor containing few (less than 100) silicon nanoparticles. The layer of silicon nanoparticles is synthesized within the oxide of this capacitor by ultra low-energy ion implantation and annealing. Current fluctuations in the form of discrete current steps and sharp peaks appeared in the static and dynamic I(V) characteristics of the capacitor. These features have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…The IR vibration bands are the typical SiO 2 vibration ones, namely: (1) Si O rocking, (3) Si O bending, (5) Si O stretching in phase, (6) Si-O stretching out of phase [11,12]; in SRO films a similar behaviour is obtained in the IR vibration bands. Besides in our SRO films, (2) Si H wagging and (4) >Si H bending vibrations are associated to hydrogen [13,14] (2) decreases (see inset in Fig. 3).…”
Section: Resultsmentioning
confidence: 89%
“…The IR vibration bands are the typical SiO 2 vibration ones, namely: (1) Si O rocking, (3) Si O bending, (5) Si O stretching in phase, (6) Si-O stretching out of phase [11,12]; in SRO films a similar behaviour is obtained in the IR vibration bands. Besides in our SRO films, (2) Si H wagging and (4) >Si H bending vibrations are associated to hydrogen [13,14] (2) decreases (see inset in Fig. 3).…”
Section: Resultsmentioning
confidence: 89%
“…For instance, a MOS capacitor showed a better retention time of charges in the Si-NCs reservoir, and some quantized charging effects [5]. The emission intensity was also dramatically increased, and the PL energy was shifted according to the average Si-NCs size measured by electron microscopy [6].…”
Section: Introductionmentioning
confidence: 89%
“…Recently, it was shown that annealing in a mild oxidizing atmosphere (either at the same time that the NC growth phase or during a second annealing following the initial growth phase) strongly improved both the electrical and optical properties of these systems [5][6]. For instance, a MOS capacitor showed a better retention time of charges in the Si-NCs reservoir, and some quantized charging effects [5].…”
Section: Introductionmentioning
confidence: 99%
“…Such effects could be obtained at room temperature if Sinp's were small enough (<10 nm), in such a way that the charging energy for adding one electron to a Si-np becomes larger than the thermal energy (>26 meV) [5], and single electron memories could be done. These quantum effects has been observed in the form of current peaks and discrete steps and associated with charge trapping into and de-trapping from nanoparticles [5].…”
mentioning
confidence: 99%
“…[1][2][3][5][6][7]. However, compatible techniques with complementary metal oxide semiconductor (CMOS) are preferred.…”
mentioning
confidence: 99%